Marketing Communication Strategy Analysis (Case Study of Marketing Communication Strategy at Gallery RJ via Instagram @Gallery RJ Bengkulu) - Riswanto; Aldo Sigananta (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
This study aims to determine the marketing communication strategy of Gallery RJ through Instagram @Gallery RJ Bengkulu. The type and approach of the research used are qualitative with descriptive methods. Inflorman in this study was obtained from purposive sampling techniques. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques used were data reduction, data presentation, and conclusions. The conclusion of this study is that the marketing communication strategy of Gallery RJ through Instagram @GalleryRJ Bengkulu has proven effective in increasing product promotion and sales by utilizing various Instagram features such as photo uploads, visual effects, informative captions, tags, and hashtags. The application of the AISAS concept (Attention, Interest, Search, Action, Share). 1). Attention (Attention), promotions can attract the audience's attention to a product or brand through interesting and relevant content. 2). Interest (Interest): after getting attention, promotions can build audience interest by highlighting product benefits, unique features, or positive experiences they have felt. 3). Search (Search): interested audiences may seek further information about the product or service being promoted, either through online searches or direct inquiries. 3). Action: Promotions can encourage audiences to take action, such as visiting a website, purchasing a product, or participating in a marketing campaign. 4). Share: If audiences are satisfied with a product or service, they are more likely to share their positive experience with others, both online and offline, which can increase brand awareness and expand marketing reach.